2016
DOI: 10.18203/2349-3291.ijcp20160060
|View full text |Cite
|
Sign up to set email alerts
|

The management of complicated airway foreign bodies in children: our institutional experience

Abstract: INTRODUCTIONForeign body (FB) aspiration is typically seen in preschool children. 1,2,4Exploring nature and inquisitiveness of these babies is commonly attributed for FB aspiration. 2,4,5 The majority of acute foreign body aspirations presents dramatically and can be safely extracted with rigid or flexible bronchoscopy with optical forceps.5 However, on rare occasions these patients may present with complications related to FB impaction and its effects distal to it. We present our study on complicated airway F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Elaziz, M.A., et al [2] have also performed bronchotomy, but their experience was limited to pediatric cases only. Aihole JS et al [3] reported their experience, but it was also limited to pediatric cases only. So far, the experience of surgical retrieval of impacted foreign bodies in adults is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Elaziz, M.A., et al [2] have also performed bronchotomy, but their experience was limited to pediatric cases only. Aihole JS et al [3] reported their experience, but it was also limited to pediatric cases only. So far, the experience of surgical retrieval of impacted foreign bodies in adults is limited.…”
Section: Discussionmentioning
confidence: 99%
“…plicated FBA and are strategic (15)(16)(17)(18). In a study by Fraga et al (19), the authors report a case of an 8-year-old boy presenting with an airway foreign body that was too large to be extracted through the subglottic region.…”
mentioning
confidence: 99%